Radiation damage study of electrical properties in GaN LEDs diode after electron irradiation - Abdullah, Yusof; Hedzir, Anati Syahirah; Hasbullah, Nurul Fadzlin; Muridan, Muridan, Norasmahan; Che Hak, Cik Rohaida; Mahat, Sarimah (Scientific.Net, 2017)
Nitride-based light emitting diodes (LEDs) is an attractive material due to its high temperature tolerance and suitable to be used in extreme environment. The irradiation process of Gallium Nitride (GaN) diode was carried out by electron irradiation with 1000 kGy and 1500 kGy doses with a conveyor speed of 50 kGy per pass. Capacitance-voltage (C-V) and current-voltage (IV) characterization for both pre and post irradiation samples was done. Both current and capacitance show decreasing while reverse leakage current increased after irradiation. The reverse leakage current revealed that the current were start leakage at 1.0 x10-7 A and 1.0 x10-9 A for 1000 kGy and 1500 kGy irradiations respectively. The current-voltage graph indicated that the effect of electron irradiation on diode produced weak spots as defect cause leakage current. The traps and bulk defect is believed to contributed to the leakage current increased.